In situ measurement of pH in liquid chromatography systems using a colorimetric approach. Issue 3 (21st December 2018) - Leme, Gabriel; Madigan, Benjamin; Eikens, Joseph; Harmes, David C.; Richardson, Douglas; Carr, Peter; Stoll, Dwight
Abstract : In liquid chromatography differences between the pH of an injected sample and the pH of the mobile phase can have a significant impact on retention times, peak widths, and resolution. Abstract : In liquid chromatography differences between the pH of an injected sample and the pH of the mobile phase can have a significant impact on retention times, peak widths, shapes, and resolution. When the injection volume is negligibly small relative to the column volume this is typically not a problem. However, when the injected volume becomes large enough, and both the pH and buffer capacity discrepancies are significant, there will be a zone of sample that travels through the column without mixing with the surrounding mobile phase, and thus the pH of this zone will be that of the sample rather than the column eluent itself. We have studied situations like this in detail, specifically in the case of two-dimensional liquid chromatography where the composition (pH and concentration) of the first dimension eluent which carries the sample is quite different from the second dimension eluent into which it is injected. In this paper we describe a colorimetric approach for the in situ determination of the pH in LC systems thus enabling more detailed studies of pH changes at different points inside the system. We find that this approach is complementary to existing technologies for inline pH measurement ( e.g., ion selective electrodes) in that it can be implemented with a UV detector, can be used at high pressures, is easy to use, and is sufficiently reproducible to be useful in this context.